Isolation, Identification and Ethanol Production of Indigenous Yeast of Toddy Palm (Borassus Flabellifer L.) Juice From Tuban, East Java, Indonesia - Ekwan Nofa Wiratno; Novi Soleman Rupilu (University of Brawijaya, 2018)
This study aimed to obtain and identify the indigenous yeasts isolated from Borassus flabellifer L. juice and its potency in ethanol production. Steps of this study included isolation, enumeration, characterization, identification and ethanol production and measurement of ethanol concentrations and medium acidity during fermentation. The yeast total isolated from Borassus flabellifer L. juice was 5.06 x 105 CFU/mL and the isolate U2 was phenotypically identified as Candida tropicalis (95.7% ID and T = 1). The pH level of medium decreased during the ethanol fermentation. Yeast isolate U2 was able to produce ethanol by 140.1 g/L using 50 g/L of glucose and it was not significantly different with ethanol yield fermented by Saccharomyces cerevisiae (148.6 g/L).